Illegal wildlife trade: Indonesian turtle egg traders in Kalimantan-Sarawak border - Khalil Ur Rehman, Arif Jawaid, Parveen Kaur, Nurul Nadzatul Farah Binti Mohd Khairi, (Opción, 2019)
This study investigates illicit trafficking of turtle eggs across Kalimantan-Sarawak border, who are the individuals or organizations involved, what motivates people to engage in illegal wildlife trade. Interviews with five offenders which are identified through snowball sampling technique and observations were conducted. As a result, the offenders from Kalimantan region, are motivated to sell the eggs in order to support their family as a secondary income besides selling their legal goods in Bau. In conclusion, the easy access in obtaining the eggs from Kalimantan as well as high demand from the locals further supports the continuity of this illegal activity.